The Swedish Exercise Self-Efficacy Scale (ESES-S): reliability and validity in a rheumatoid arthritis population. (23rd October 2015) - Nessen, Thomas; Demmelmaier, Ingrid; Nordgren, Birgitta; Opava, Christina H.
Abstract: Purpose : The aim of the present study was to investigate aspects of reliability and validity of the Exercise Self-Efficacy Scale (ESES-S) in a rheumatoid arthritis (RA) population. Methods : A total of 244 people with RA participating in a physical activity stkudy were included. The six-item ESES-S, exploring confidence in performing exercise, was assessed for test–retest reliability over 4–6 months, and for internal consistency. Construct validity investigated correlation with similar and other constructs. Results : An intraclass correlation coefficient (ICC) of 0.59 (95% CI 0.37–0.73) was found for 84 participants with stable health perceptions between measurement occasions. Cronbach's alpha coefficients of 0.87 and 0.89 were found at the first and second measurements. Corrected item-total correlation single ESES-S items ranged between 0.53 and 0.73. Construct convergent validity for the ESES-S was partly confirmed by correlations with health-enhancing physical activity and outcome expectations respectively (Pearson's r  = 0.18, p  < 0.01). Construct divergent validity was confirmed by the absence of correlations with age or gender. No floor or ceiling effects were found for ESES-S. Conclusions : The results indicate that the ESES-S has moderate test–retest reliability and respectable internal consistency in people with RA. Construct validity was partially supported in the present sample. Further research on construct validity of the ESES-S is recommended. Implications for Rehabilitation: Physical exercise is crucial for management of symptoms and co-morbidity in rheumatoid arthritis. Self-efficacy for exercise is important to address in rehabilitation as it regulates exercise motivation and behavior. Measurement properties of self-efficacy scales need to be assessed in specific populations and different languages.